Who Is Manya Curie? Biography of Famous People Children's Biography Books - Baby Professor (United States Baby Professor, 2017)
Marie Curie made a very important discovery in the field of chemistry. She invented the word radioactivity. It was a significant milestone in science because it gave scientists the knowledge on how to treat radioactive substances. Without Marie Curie, we would be living in a dangerous world today. Learn from her story by reading this book today
Keywords: Biography -- Biography